2019
DOI: 10.30848/pjb2019-6(6)
|View full text |Cite
|
Sign up to set email alerts
|

Improving phosphorus efficiency and productivity of wheat by application of manure amended phosphate fertilizer

Abstract: Phosphorus (P) efficiency from inorganic fertilizers is very low and major cause of lower crop productivity, thus proper remedy is required for maintaining optimum P supply from soil to ensure higher wheat productivity. Two-years (2015-16 & 2016-17) field trials have shown that application of phosphoric acid (PA) at 54 kg P ha-1 along with farmyard manure (FYM) produced maximum wheat grain (5159 kg ha-1), 23% higher over its sole application. Phosphorus uptake was increased with the increase in P rates (18, 36… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In China, as in other countries of the world, only 20% of P fertilizer is taken up by crops in the first growing season after application (Zhang et al, 2007). Many previous studies have found that manure can be used as alternative P fertilizer, which can improve efficiency of inorganic fertilizers and enhance wheat productivity grown in alkaline calcareous soils (Cordell et al, 2009;Achat et al, 2014;Ikram et al, 2019a;Ikram et al, 2019b;Akhtar et al, 2020). Besides, a substantial part of applied P accumulates in the soil as so-called legacy P (Rowe et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In China, as in other countries of the world, only 20% of P fertilizer is taken up by crops in the first growing season after application (Zhang et al, 2007). Many previous studies have found that manure can be used as alternative P fertilizer, which can improve efficiency of inorganic fertilizers and enhance wheat productivity grown in alkaline calcareous soils (Cordell et al, 2009;Achat et al, 2014;Ikram et al, 2019a;Ikram et al, 2019b;Akhtar et al, 2020). Besides, a substantial part of applied P accumulates in the soil as so-called legacy P (Rowe et al, 2015).…”
Section: Introductionmentioning
confidence: 99%